Od populizmu regionalistycznego do nacjonalistycznego: Refleksja nad włoskim populizmem na przykładzie Ligi (Północnej) (Politeja, 2020)
From Regionalistic to Nationalistic Populism. Reflection on Italian Populism on the Example of the (Northern) LeagueThe (Northern) League has been playing a key role on the Italian political scene for almost three decades. The article approaches the issue of the elements of rhetoric of the populist narrative proclaimed by the party with particular emphasis on the two types of populism: regionalistic and nationalistic populism. The purpose of the article is above all an attempt to reconstruct the most important populist characteristics and activities contributing to the League’s significant electoral success and verification of the research hypothesis that the phenomenon of populism in Italy is associated with the long‑standing regional character of the Italian state and the resulting attitude of putting their (often regional) interests above those of others.